Unemployment benefits and reservation wages: key elasticities from a stripped-down job search approach - John T. Addison; Mário Centeno; Pedro Portugal (Institute for the Study of Labor (IZA), 2008)
This paper exploits survey information on reservation wages and data on actual wages from the European Community Household Panel to deduce in the manner of Lancaster and Chesher (1983) additional parameters of a stylized structural search model; specifically, reservation wage and transition/duration elasticities. The informational requirements of this approach are minimal, thereby facilitating comparisons between countries. Further, its policy content is immediate insofar as the impact of unemployment benefit rules and measures increasing the arrival rate of job offers are concerned. These key elasticities are computed for the United Kingdom and eleven other European nations.
Keywords: J64; 330; Reservation wages; probability of reemployment; accepted wages; unemployment benefits; arrival rate of job offers; wage offer distributions; Arbeitsuche; Anspruchslohn; Elastizität; Arbeitslosenversicherung; Berufliche Integration; Vergleich; EU-Staaten; Großbritannien